Integrated transport system of agglomerations as a factor of economic growth ("Journal "U". Economy. Management. Finance.", 2022)
This article discusses the development of the transport system in agglomerations. The role of developed transport infrastructure in modern conditions of agglomeration development is determined. Transport accessibility is an important factor in the development of megacities. The existing problems of modern transport systems of agglomerations are revealed. Directions for the development of an integrated transport system have been formed, such as the interaction of all types of public urban transport to ensure equal accessibility of transport services.
Keywords: agglomeration; integrated transport system; transport services; modernization; carrying capacity; public urban transport